Reproductive performance of cat breeds in Bangladesh (Bangladesh Veterinarian, 2025)
This study was carried out in the Rangpur Division, Bangladesh, to identify domestic cat breeds and assess their reproductive performance. Data were obtained through direct questionnaire administered to cat owners, complemented by regular observation of breed characteristics, behaviour, and reproductive traits. Ten breeds were identified: Indigenous, Persian, Persian (Calico), Maine Coon, Bengal Cat, Mixed, British Shorthair, Turkish Angora, Scottish Fold and American Shorthair. Common oestrus signs included vocalization, rolling, rubbing of the body and genital area, affectionate behaviour, and receptivity to male. The age at sexual maturity among females ranged from 6 to 23 months, with Persian cats exhibiting the highest mean age at maturity (16.2 ± 3.8 months, P